INTRODUCTION TO THE SOLAR SYSTEM USING AUGMENTED REALITY TECHNOLOGY AS PRIMARY SCHOOL LEARNING MEDIA - Imam, Muhamad Imam; Rohim, Nana Rusdiana; Triono, Wahyu (INTI TALAFA, 2025)
Teaching about the solar system at the primary school level often faces various challenges. One of them is the lack of interactive media, so learning is still limited to textbooks and illustrations. In recent years, rapid developments in information and communication technology have brought significant progress. One of them is through the presence of Augmented Reality (AR) technology. This research aims to facilitate the learning process of students at school as well as help parents in explaining the concept of the solar system. This research uses the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: conceptualisation, design, material collection, assembly, testing, and distribution. The result of this design and testing process is an Augmented Reality technology-based solar system introduction learning system aimed at elementary school students. The developed application functions as an interactive practicum media, with material that has been adapted to the needs and level of understanding of elementary school children. Keywords: Introduction, Augmented reality, Solar System, Primary School, Unity